Design of Online Library Information System at Sei Kamah Village Hall I - Musthafa Haris Munandar; Syaiful Zuhri Harahap; Masrizal; Rahma Muti ah; Yeni Syahfutri S (Jurnal Mantik, 2020)
The research results suggest that the collection of books available in Balai Desa Sei Kamah I Library is still insufficient. The book collection only has a ratio of 1:5 compared to the number of users. The utilization rate of book collection by sei kamah I villagers is also low. When in the library, the community, especially among students, is deficient in visits to the library. In one week, the community only 1 or 2 times came to the library and spent less than 1 hour. Library employees and staff have not played a full role in promoting how important a library is. Therefore, researchers created a new idea that the library system that is still manual is made into an Online-based system. The library service becomes better and more enjoyable.